PROFESSIONAL SKILL COMPETITIONS AS A COMPONENT OF LIBRARIANS ADVANCED TRAINING - Dolmatova, Nina (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Questions of librarians advanced training with use of various forms and methods, including professional skills competitions are discussed in this article. Practical experience is also represented